In vitro and in vivo evaluation of the duck's feet collagen sponge for hemostatic applications. (October 2017) - Seo, Ye Been; Lee, Ok Joo; Sultan, Md. Tipu; Lee, Jung Min; Park, Ye Ri; Yeon, Yeung Kyu; Lee, Ji Seung; Lee, Young Jin; Kim, Soon Hee; Park, Chan Hum
Recently different hemostatic agents have been developed, but most of them are ineffective in severe bleeding and expensive or cause safety concerns. In this study, we fabricated duck's feet collagen-based porous sponges and investigated its use as a hemostatic agent. We determined the sponge's physical and biological characteristics and compared with Avitene via scanning electron microscope analysis, water-uptake abilities and porosity test, and cytotoxicity assay. The duck's feet collagen/silk sponge showed a larger interconnected porous structure compared to others sponges. The duck's feet collagen/silk sponge also exhibited significantly higher porosity than Avitene. Hemostatic properties of the sponges were evaluated by whole blood clotting and rat femoral artery hemorrhage experiment. The addition of silk to duck's feet collagen showed better blood clotting ability than Avitene in vitro. However, rat femoral artery hemorrhage test showed a similar hemostatic property between the duck's feet collagen-based sponges and Avitene. We suggest that duck's feet collagen-based sponge can be effectively used for hemostatic applications.